2019
DOI: 10.1002/chir.23059
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic approach to study the configurational stability of Ni(II) complexes of amino‐acid Schiff bases possessing stereogenic nitrogen

Abstract: Herein, we disclose the design of a model Ni(II) complex of glycine Schiff base possessing single-nitrogen stereogenic center, which was successfully used for high-performance liquid chromatography (HPLC)-assisted assessment of its configurational stability. The major finding is that the configurational stability of the Ni(II)-coordinated nitrogen is profoundly dependent on the reaction conditions used, in particular the solvent, and can range from inconsequential (t ½ less than 5 min) to virtually completely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Recently, we demonstrated that Ni(II)‐complex 5 (Scheme ) can be successfully used to assess its configurational stability of the stereogenic nitrogen via HPLC assisted kinetic racemization experiments 10a. Our preliminary studies served as a convincing demonstration of the viability of the chosen HPLC‐based approach for working with Ni(II) complexes of AA Schiff bases. In particular, for Ni(II) complex 5 , we reported that the configurational stability of the Ni(II)‐coordinated nitrogen significantly depends on the solvent used for the experiments.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Recently, we demonstrated that Ni(II)‐complex 5 (Scheme ) can be successfully used to assess its configurational stability of the stereogenic nitrogen via HPLC assisted kinetic racemization experiments 10a. Our preliminary studies served as a convincing demonstration of the viability of the chosen HPLC‐based approach for working with Ni(II) complexes of AA Schiff bases. In particular, for Ni(II) complex 5 , we reported that the configurational stability of the Ni(II)‐coordinated nitrogen significantly depends on the solvent used for the experiments.…”
Section: Resultsmentioning
confidence: 79%
“…While reported in the previous work,10a data provided detailed and instructive understanding of the chiral nitrogen configurational stability in relationship to the reaction solvent, the effect of substituents on the nitrogen as well as the coordinating metal remained totally unknown. Thus, drawing inspiration from the success of the previous study,10a we designed a new set of the stereochemical models presented in Scheme .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Complexes of Schiff bases play an important role in the detection of various ions, exhibit biological properties, and are widely used as catalysts . Recently, several studies focused on Schiff bases and their complexes, derivatives of natural products, for example, amino sugars, amino acids, and chitosan . Identifying new enantiomerically pure systems is one of the major goals of organic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…[4,11,12] Recently, several studies focused on Schiff bases and their complexes, derivatives of natural products, for example, amino sugars, amino acids, and chitosan. [7,[13][14][15][16][17][18][19][20] Identifying new enantiomerically pure systems is one of the major goals of organic chemistry. Although the number of papers published on Schiff bases is increasing every year, they still have a huge potential and are promising ligands of metal complexes.…”
Section: Introductionmentioning
confidence: 99%